Media Edukasi Permainan Ular Tangga Meningkatkan Pengetahuan Siswa Sekolah Dasar dalam Menghadapi Bencana Gempa Bumi - Dharma Yani, Made Vina; Sukawana, I Wayan; Sukarja, I Made; Juniari, Ni Made; Wedri, Ni Made; Mertha, I Made (Jurusan Keperawatan Poltekkes Kemenkes Denpasar, 2025)
Indonesia has a high risk of disasters due to its geological and geographical location. Disasters are events that threaten society and impact all ages, including children. This shows that knowledge in dealing with disasters is very important to be given to children. This research aims to determine the effect of providing education using the snakes and ladders game on elementary school students' knowledge in dealing with earthquake disasters. The type of research is Pre- Experimental design with the design used, namely One-group pre-post design using simple random sampling. The total sample was 33 people. The variables in this study are education through the media of snakes and ladders games and elementary school students' knowledge of dealing with earthquake disasters. Knowledge data were collected using a knowledge questionnaire on dealing with earthquake disasters. Data analysis techniques were used using the Wilcoxone test. The results of the research showed that the knowledge of elementary school children before being given audiovisual media education was mostly in the sufficient category, namely 18 people (54,5%) and after being given it showed an increase in preparedness knowledge with the result that the majority of students were in the good category, 32 people (97%). The results of the research were tested using the Wilcoxon statistical test, obtained p-value = 0,000 alpha (0,05), it can be concluded that there is an influence of providing education in the snakes and ladders game media on students' knowledge in dealing with earthquake disasters at SD No. 2 Cemagi. It is recommended that teachers in schools increase the provision of disaster material by developing other similar game media.